A randomized controlled trial to evaluate a behavioral economic strategy for improving mobility in veterans with chronic pain. - Peggy Compton; Krisda H Chaiyachati; Tanisha Dicks; Elina Medvedeva; Manik Chhabra (PLoS ONE, 2021)
Rates of chronic pain and daily opioid use are higher among veterans relative to civilian populations. Increasing physical activity can reduce pain severity and decrease opioid use among patients with chronic pain. Behavioral economic strategies can improve physical activity levels but have been undertested in veterans with chronic pain. The objective of this study was to evaluate if a financial incentive combined with a loss aversion component-a "regret lottery" in which veterans could win money if they met a set goal or told how much they could have won had they met their goal-would increase physical activity levels among veterans with chronic pain. A 12-week single-blinded randomized controlled trial (ClinicalTrials.gov: NCT04013529) was designed. Veterans with chronic pain (N = 40) receiving care at a specialty pain clinic were eligible for participation, and were randomly assigned (1:1) to either (a) activity trackers and daily text message reminders to increase physical activity ("control arm"), or (b) the same plus a weekly regret lottery ("intervention arm"). For those in the intervention arm, participants who met their activity goal, had a chance to win a small ($30) or large ($100) gift card incentive; those who did not meet their goals were informed of what they would have won had they met their goal. The primary outcome, physical activity, was measured using self-reported physical activity and step counts using activity trackers. Secondary outcomes included changes in physical function, chronic pain severity, depression and opioid use. The sample was primarily white, male and disabled, with an average age of 57 years. No between-arm differences were noted for physical activity, physical function, chronic pain severity, depression or opioid use. Regret lottery-based approaches may be ineffective at increasing physical activity levels in veterans with chronic pain. Trial Registry: NCT04013529.